Chlorine dioxide fumigation improves kiwifruit peel appearance by selectively depleting flavonoid pigments without compromising eating quality - Jiacheng Teng; Rui Chen; Xuening Wu; Yanfei Hu; Zhengchen Tian; Weisong Li; Wendong Zhang; Xiaomei Ji; Xiaoqin Yang; Xuping Gong; Tiantian Li; Xiaoyan Mao; et al. (Postharvest Biology and Technology, 2026)

Elements migration revealed by scientific drilling in the Anninghe fault, western Sichuan, China: Implication for seismicity in the southeastern margin of the Tibetan plateau - Qing Wei; Xuan-Hui Yang; Jia-Yong Tian; Duo-Xing Yang; Hong-Rui Fan (Journal of Asian Earth Sciences, 2026)

Efficient sludge reduction and phosphorus recovery in innovative coupled sequencing batch and worm reactor Process: Performance, mass balance and metagenomic mechanisms - Jingjing Zhang; Lipin Li; Xuanhe Yang; Siqi Chen; Zhe Li; Rui Li; Chunlei Wang; Yu Tian (Bioresource Technology, 2026)

Nitrogen fertilization and straw returning boost soil animal energy flux via distinct trait- vs. density-driven pathways - Hangle Ren; Rui Wu; Siwen Yang; Ying Liu; Weijie Zhao; Yamin Peng; Xiaohong Tian; Rui Yin (Agriculture, Ecosystems & Environment, 2026)

Mechanisms of sedimentary phosphorus migration in response to salinization: Iron-phosphorus coupled cycling and “manganese curtain” inhibition - Rui Li; Zuobing Liang; Zaizhi Yang; Zelin Yue; Shaoheng Li; Di Tian; Zhi Zhang; Liang Xiao; Jianyao Chen; Lei Gao (Journal of Environmental Chemical Engineering, 2026)

Beyond flavor: dietary vanillyl alcohol, a D₂ receptor antagonist promoting sleep - Lijing Zhang; Yujie Yang; Dongmei Yang; Richard Ward; Zhenshuai Hu; Hao Chen; Mengli Lan; Cheng Xiang; Su An; Jiameng Dai; Ying Zhu; Xianrun Sun; et al. (Food Research International, 2026)

Mechanistic insights into the adsorption and separation of nonpolar molecules on delocalization porous carbon: Dispersion interactions enhanced by multiple bonds - Peixin Wang; Jingxu Tian; Da Wei; Yue Sun; Bo Liu; Wenji Pi; Jun Ma; Yunfeng Zhang; Hongyu Chen; Rui Shi; Yang Guo; Xiang Xu; et al. (Chemical Engineering Journal, 2026)

Spirofluorene-grafted triazine branched poly(aryl piperidinium) anion exchange membranes for high performance water electrolysis and flow batteries - Wei-Feng Yang; Yong-Xin An; Rui Guo; Han Yan; Tian-Tian Wang; Chang-Ping Liu; Yong-Mei Tian; Wen-Bin Sun (Chemical Engineering Journal, 2026)

Genesis of the Jiawula Pb–Zn–Ag deposit in the Great Xing’an Range, NE China: constraints from fluid inclusions and S–Pb isotopes - Hongzhe Xie; Guiyuan Sun; Quzong Baima; Xinyu Gao; Ziwen Yang; Rui Tian; Lin Yang; Licheng Zhao; Zhiping Li (Journal of Asian Earth Sciences, 2026)

Kosakonia oryziphila KC516 mediated growth promotion of Cosmos bipinnatus in phosphogypsum by modulating rhizosphere geochemistry and root transcriptome - Jing Zhang; Hao-Tian Dong; Yuan-Chun Yang; Rui Liu; Shuai Wang; Ao-Li Zhang; Yuan Su; Ming-Hua Dong; Yan-Ru Cao; Hua-Li Zhang (Environmental Geochemistry and Health, 2026)

Ecological risk assessment of 1,4-thioxane and its remediation by a synthetic microbiome based on a sulfur transformation system: From multi-omics to water application - Xu Yang; Ai-de Peng; Yong-han Huang; Jia-hao Cheng; Hao-tian Zhong; Hai-tang Zhou; Pei-qi Liu; Xiao-hui Ji; Chen Li; Sheng-rui Zhang; Jin-long Lai; Xue-gang Luo (Water Research, 2026)

LhCAT2-mediated crosstalk between reactive oxygen species homeostasis and anthocyanin biosynthesis enhances zinc tolerance in Liriodendron hybrid - Yongchao Ke; Yu Liu; Teja Manda; Tian Min; Rui Wang; Wenbin Su; Liming Yang (Journal of Hazardous Materials, 2026)

A legacy pollutant deciphered by multiomics toxicology and targeted remediation by a synthetic microbial consortium: a case study of 2-chloroacetophenone from abandoned chemical weapons - Xu Yang; Ai-De Peng; Jia-Hao Cheng; Yong-Han Huang; Hao-Tian Zhong; Hai-Tang Zhou; Pei-Qi Liu; Xiao-Hui Ji; Chen Li; Sheng-Rui Zhang; Jin-Long Lai; Xue-Gang Luo; et al. (Water Research, 2026)

Underground mine tunnel fire dynamics: Experimental investigation and AI-driven characterization of flame behavior - Jingmin Xu; Rui Tian; Ashish Kakoria; Aamir Iqbal; Tao Yang; Lina Zheng; Guang Xu (Tunnelling and Underground Space Technology, 2026)

Organic acids in four representative fermented alcoholic beverages: absorption, metabolic fate, and molecular mechanisms of health benefits - Xiaolu Tian; Rui Zhang; Haijue Zhang; Yi Liang; Yunxiang Ma; Zixuan Yang; Fuliang Han (Critical Reviews in Food Science and Nutrition, 2026)

Hierarchical Studies in TRAP2 Mice Demonstrate that Neuronal Activation and Mitochondrial Networks Integration Constitute the Key Mechanism Underlying Painful Syncope - Xueyin Pu; Yulu Xia; Ziwei Ni; Changlei Zhu; Kunlong Zhang; Bozhi Liu; Rui Lin; Jingxuan Zhu; Hui Liu; Shujiao Li; Yunqiang Huang; Feifei Wu; et al. (Neuroscience Bulletin, 2026)

Control of zeolite local microenvironment by organofluorination engineering toward efficient c-C4F8/C3F8 separation - Rui Sun; Zicheng Wan; Yaqi Wu; Yaohan Fu; Yang Zhang; Chenyang Yang; Heng Zhao; Ziqi Tian; Liang Chen (Chemical Engineering Journal, 2026)

Spatial and environmental niche differentiation facilitates sympatric macaques' coexistence in montane-canyon landscapes: Implications for conservation - Wei Zhou; Yuan Wang; Deyan Ge; Qisen Yang; Gang Song; Jilong Cheng; Tian Tian; Yu Zhang; Jinbo Xu; Ying Liu; Weibo Wang; Xiaochuan Wang; et al. (Biological Conservation, 2026)

Cross-instrument coal quality spectral analysis via a PDS-assisted fine-tuning calibration transfer method - Junlong Gao; Jiaxuan Li; Jiaxin Yin; Rui Gao; Zhihui Tian; Yang Zhao; Yu Bai; Lei Dong; Weiguang Ma; Lei Zhang; Wangbao Yin; Suoteng Jia (Analytica Chimica Acta, 2026)

SYVN1-provoked RASA1 ubiquitination promotes pulmonary inflammation in chronic obstructive pulmonary disease - Ju-Hong Wu; Yi-Cheng Ma; Yu-Qi Wang; Hai-Long Miao; Meng-Xue Liu; Dong-Xu Hua; Min-Min Tang; Tian-Rui Sui; Zhi-Yong Wu; Yu Wang; Jin Yang; Hui Zhao; et al. (Inflammation Research, 2026)

Ascosphaera apis-derived microRNA-like RNAs mediate cross-kingdom regulation of gene expression in western honeybee larvae - Xiaoxue Fan; Nian Fan; Tao Wu; Jing Kang; Jiarun Yang; Jing Tian; Xihan Luo; Dafu Chen; Jianfeng Qiu; Rui Guo (Journal of Invertebrate Pathology, 2026)

Efficacy and Safety of Intravenous Thrombolysis with Tenecteplase in Patients with Wake-Up Branch Atheromatous Disease - Lili Zhu; Ying Zhang; Jiarong Li; Liang Song; Haoran Li; Yang Yang; Lijuan Liu; Shaolei Zhang; Xiaofei Gao; Weifeng Chen; Guo Rui; Haiqiang Qin; et al. (Translational Stroke Research, 2026)
Branch atheromatous disease (BAD), a subtype of acute ischemic stroke (AIS), is associated with a high risk of early neurological deterioration (END) and poor prognosis. Wake-up stroke (WUS), comprising 20%–30% of AIS cases, is typically excluded from thrombolysis because of unknown onset time. Using diffusion-weighted imaging/fluid-attenuated inversion recovery (DWI/FLAIR) mismatch, we evaluated the efficacy and safety of Tenecteplase (TNK) thrombolysis in patients with BAD-related WUS. We retrospectively recruited 1,062 patients from seven Zhengzhou hospitals between January 2021 and June 2025. The patients received either TNK (n = 338) or dual antiplatelet therapy (n = 724). Propensity score matching (PSM; 1:1, caliper 0.02) yielded 292 matched pairs. Early neurological changes were evaluated using the National Institutes of Health Stroke Scale (NIHSS), and 90-day outcomes were evaluated using the modified Rankin Scale (mRS). After PSM, TNK significantly reduced the risk of END (odds ratio [OR] = 0.425, 95% confidence interval [CI]: 0.262–0.689; P < 0.001). Patients treated with TNK were more likely to achieve good functional outcomes (modified Rankin Scale [mRS] 0–1 and 0–2) with fewer poor outcomes (mRS ≥ 4). There were no significant differences in symptomatic intracranial hemorrhage, other bleeding events, or mortality among the groups. DWI/FLAIR mismatch-guided TNK thrombolysis appears to overcome the limitations of an unknown onset time in WUS and may counteract the progressive pathophysiology of BAD. TNK intravenous thrombolysis may be a safe and effective treatment for patients with wake-up BAD and DWI/FLAIR mismatches.

High-Frequency Signal Recovery via the Constraint of Reflection Structure in f-x Domain - Chong Sun; Nan-ying Lan; Duo-ming Zheng; Hao-nan Tian; Shi-kai Jian; Lang Yang; Zhi-fang Ran; Rui-dong Liu (Applied Geophysics, 2026)

Muscone Exerts Rapid Antidepressant Effects Through Modulating Glutamatergic Neural Transmission in the Anterior Cingulate Cortex Against Peripheral Inflammation-induced Depression - Xiaoyun Qiu; Xiaojie Zhang; Yuanzhi Yang; Minjuan Sun; Xiaoli Da; Jiaying Liu; Rui Wang; Jingjia Liang; Xuhong Jiang; Gang Tian; Qiyuan Shan; Yu Du; et al. (Neuroscience Bulletin, 2026)

New 14,15-dinor- neo -clerodane and neo -clerodane diterpenoids from Ajuga macrosperma Wall. ex benth - Yi-huan Li; Yi-hang Ba; Jian-fen Xiao; Shuai Chen; Tian-qing Zhu; Kai-xiang Liu; Hong-ping He; Hua-yi Jiang; Rui Yang (Natural Product Research, 2026)

Chang’e-6 lander reveals local hour-scale temporal variations in lunar surface water - Honglei Lin; Heng-Ci Tian; Sheng Gou; Wei Yang; Jinning Li; Li Liu; Kai Fan; Sen Hu; Rui Xu; Zhiping He; Yong Wei; Yangting Lin (Science Bulletin, 2026)

Bioaerosol emission in public washroom under different time intervals of working day and critical exposure time for sanitary workers - Wajid Ali; Zi-qi Yang; Chun-shu Tian; Rui-wen Li; Xu Zhang; Qing Yan; Ke-yu Chen; Si-bo Cheng; Rong-xin Wang; Cheng Yan (Building and Environment, 2026)

The association of long-term exposure to PM1 with dyslipidemia in Chinese older adults and the modifying role of vitamin D - Pengjing Yao; Rui Zhang; Xuqiu Cheng; Xinyu Kou; Ziwei Tian; Jinmin Zheng; Yan Zhang; Xianwei Guo; Bing Hu; Changliu Liang; Yufeng Wen; Fangbiao Tao; et al. (Atmospheric Pollution Research, 2026)

Cell-specific gene expression plasticity in response to hypoxia promotes high-altitude adaptive evolution - Wen-Tian Wei; Ze Yan; Hui Wu; Ming-Liang Zhou; Dong-Xin Mo; Xing Wan; Rui Ma; Mei-Ming Wu; Jia-Hui Huang; Ya-Jing Liu; Ji Yang; Meng-Hua Li (Science China Life Sciences, 2026)

High-value utilization of chromium ore processing residue (COPR) through corn straw-soda roasting followed leaching processes - Cheng Tian; Zilong Li; Cunfang Lu; Rui Xu; Min Zhang; Lin Yang; Wenlin Xie; Zhengnan Zhong; Yuanyuan He; Juan Wen; Dan Luo (Journal of Environmental Chemical Engineering, 2026)

Triple-synergistic nanotherapeutics for acute and chronic colitis management via programmable multidimensional modulation - Penghui Wang; Yue Zhao; Ning Tian; Xiangling Liu; Tenghui Tian; Difu Zhu; Fangbing Liu; Hengyan Liu; Ling Li; Zhiyu Ren; Deok Chun Yang; Lei Zhao; et al. (Chemical Engineering Journal, 2026)

Dynamic electric field modulation via BaTiO3-based staggered-type heterojunction for all-solid-state lithium-sulfur batteries - Yancheng Yang; Sizhe Wang; Fei Liang; Haizhou Zhao; Yi Gu; Rujing Liu; Jian Sun; Yao Yao; Rui Tian; Haojie Song (Chemical Engineering Journal, 2026)

Interactive effects of microplastics, heavy metals, and soil microecology under different irrigation water sources - Rui Yang; Lijuan Huo; Hao Yang; Yan Gong; Gaiqiang Yang; Shuting Tian; Shuhui Cao; Xia Li; Qingwei Ding; Yaqiong Fan; Qi Liu (Applied Soil Ecology, 2026)

Multi-omics reveals that Sophora alopecuroides lysine decarboxylase (SaLDC)-mediated polyamine metabolism enhances salt tolerance and early flowering in Arabidopsis - Yongli Tian; Rui Wang; Jing Su; Wenjuan Li; Ping Liu; Chengke Luo; Jiaojiao Qian; Danting Zhang; Peifu Li; Bin Wang; Rong Yang; Tianli Ma; et al. (Plant Science, 2026)

Synergistic recovering Fe, Al and biochar through biomass-reduction alkali roasting and wet magnetic separation for red mud (RM): behavior and mechanism - Rui Xu; Cunfang Lu; Min Zhang; Cheng Tian; Dan Luo; Lin Yang; Wenlin Xie; Zhengnan Zhong; Juan Wen (Minerals Engineering, 2026)

Four decades of Landsat data reveal the evolution of nitrogen and phosphorus components driven by human activities in the northern South China Sea - Di Tian; Xinfeng Zhao; Xingxian Li; Lei Gao; Zuobing Liang; Rui Li; Shaoheng Li; Zaizhi Yang; Chengxiang Sun; Jianyao Chen (Journal of Environmental Management, 2026)

New insights into deep nitrogen removal in WWTP effluent: Performance and mechanisms of autotrophic denitrification filters - Xinxin Tian; Rui Yang; Haoyong Li; Xinying Liu; Yan Dang (Journal of Environmental Management, 2026)

Opposite effects of R1234yf on the flammability limits of R600a refrigerant: Experimental and kinetic insight - Xueyan Wang; Shanzhu Hu; Rui Sun; Hua Tian; Gequn Shu; Zhao Yang (International Journal of Refrigeration, 2026)

Imidacloprid exposure at population-relevant doses induces hepatic lipid dysregulation: Exploring the role of cGAS-STING pathway-mediated hepatocyte senescence - Yuhan Zhang; Yuqing Dai; Yihong Di; Bing Wu; Xueyan Tian; Limeng Xiong; Zeyang Bai; Jinhao Jia; Jiaming Fu; Xiaoyu Li; Yi Zhao; Hao Hu; et al. (Environmental Research, 2026)

Research progress on quorum-quenching strategies for membrane biofouling control - Hongwei Wu; Kuo Yang; Yifan Gao; Rui Xu; Yuzhang Feng; Yinning Wang; Huimin Lin; Siqi Hu; Gege Tian; Jiaying Li; Pingfeng Yu; Bing Zhang (ENGINEERING Environment, 2026)

Correction to: Unveiling Differences in Source Apportionment and Optical Properties of Wintertime Carbonaceous Aerosols in Northern and Southern Chinese Cities - Rui Li; Qiyuan Wang; Jie Tian; Yong Zhang; TingTing Wu; Lu Qi; Yang Chen; Shaofei Kong; Suixin Liu; Jin Wang; Julian Shi; Yuemei Han; et al. (Aerosol Science and Engineering, 2026)

Antioxidant activity and emulsifying properties of Dendrobium officinale polysaccharides with distinct structural characteristics - Cunchao Zhao; Weiqian Wang; Fanrui Li; Jun Sheng; Rui He; Lijun You; Yang Tian (Food Chemistry, 2026)

Quantified passivator deposition via drop-on-demand inkjet printing for high-efficiency inverted perovskite solar cells - Jinxin Yang; Hengyi Jiang; Rui Yang; Ziqi Zhu; Yaxi Liu; Lina Shen; Yalian Weng; Chengbo Tian; Liqiang Xie; Zhanhua Wei (Chemical Engineering Journal, 2026)

Phosphorus remobilization triggered by reduction of manganese oxyhydroxides in newly-deposited estuarine sediments under warming conditions: Robust evidence from field investigations and a microcosm experiment - Rui Li; Zuobing Liang; Qirui Wu; Zaizhi Yang; Chenchen Yang; Di Tian; Shaoheng Li; Jianyao Chen; Lei Gao (Journal of Hydrology, 2026)

Grassland soil seed bank responses to grazing exclusion: a global synthesis - Jishuai Su; Lixin Yu; Rui Tian; Wanbing Liu; Ruolin Zhao; Menghan Niu; Zekai Yang; Yi Zhang; Fengwei Xu; Heyong Liu; Yong Jiang (Journal of Environmental Management, 2026)

Dietary components cooperate with intestinal flora to regulate food allergy - Jiaxi Yan; Li Niu; Wei Wang; Rui Gao; Jianxiong Hao; Huan Rao; Dandan Zhao; Xueqiang Liu; Wentong Xue; Yang Tian (Food Chemistry, 2026)

N6-methyladenosine attenuates tumor-associated macrophages M2 polarization via suppressing the translation of Snail - Yifan Tian; Jianxin Peng; Jiawang Zhou; Weifeng Yang; Yanxi Peng; Jianing Li; Yalan Rui; Haisheng Zhang; Guoyou Xie; Haoran Wang; Jiamin Wang; Jiexin Li; et al. (Science China Life Sciences, 2026)

Curcumin Ameliorates Depressive-like Behaviors by Modulating mGluR2/PGC-1α-Mediated Glutamatergic Homeostasis and Mitochondrial Function - Liping Xu; Deyun Jiang; Lujing Yang; Conghua Ji; Rong Bai; Yirun Xu; Tian-Rui Xu (Molecular Neurobiology, 2026)

Associations of Paternal Seminal Plasma Metals with their Spouses’ Unexplained Recurrent Spontaneous Abortion (URSA) Risk and the Potential Mediating Role of Oxidative Stress - Hanyan Xi; Rui Yang; Huaqiong Bao; Huiru Li; Youzhu Li; Francis L. Martin; Wei Chen; Liang Chen; Yan Sun; Yan-Yang Lu; Qingyu Huang; Meiping Tian (Biological Trace Element Research, 2025)

Dielectric heating technology assisted for multi-objective processing of agricultural products: research progress, challenges, and future perspectives - Mengge Li; Yingqi Tian; Gaoji Yang; Liumin Fan; Longlong Jiang; Rui Li; Shaojin Wang (Critical Reviews in Food Science and Nutrition, 2025)

The detection method of ammonia nitrogen concentration in water bodies based on hyperspectrum - Yahe Di; Tao Li; Hui Ran; Rui Yang; Fei He; Aixuan Li; Chenzhan Tang; Wenjing Tian (Journal of Water Process Engineering, 2025)

New insights into sink-source dynamics of mangrove for microplastics: Quantitative evidences from field observation and resuspension simulation - Rui Li; Chao Yan; Qirui Wu; Xiangmei Cheng; Hua Wang; Zaizhi Yang; Zuobing Liang; Di Tian; Ning Yuan; Lei Hou; Lei Gao (Journal of Hazardous Materials, 2025)

DoLPHiN: a proposed architecture and technical implementation of a database of structural and functional properties of natural polysaccharides with health benefits - Yefu Xin; Yongling Cao; Shuheng Yang; Junhao Hu; Miao Tian; Jian Dai; Jing Shi; Bingcong Yu; Nike Gu; Xiangxu Hu; Rui Zhu; Qianni Duan; et al. (Food Chemistry, 2025)

A high strength, breathable, water resistant chitosan-gelatin composite film modified by tannic acid-synergistic ZIF-8 for blueberry preservation - Huixuan Zhang; Xue Yang; Yingying Zhang; E. Zhao; Haimiao Tian; Keshan Wang; Ning Ji; Yuanyuan Liu; Rui Wang (Food Packaging and Shelf Life, 2025)

Imidacloprid induces abnormal glucose metabolism through NF-κB-mediated apoptosis of pancreatic β cells based on population exposure levels - Zhongyuan Zhang; Jiaming Fu; Yihong Di; Honghui Li; Bing Wu; Xueyan Tian; Meiyan Li; Yuqing Dai; Zhuoheng Shen; Jinhao Jia; Zeyang Bai; Limeng Xiong; et al. (Environmental Research, 2025)

Genetic loci and functional genes conferring deep-sowing tolerance across multiple environments in soybean - Rui Tian; Zhenqi Shao; Hua Zhang; Xinzhu Xing; Jiahao Chu; Youbin Kong; Zhanwu Yang; Wenlong Li; Hui Du; Huifeng Ke; Xihuan Li; Caiying Zhang (Theoretical and Applied Genetics, 2025)

CRP and HNF1A collaborate to regulate the progression of laryngeal cancer through the Wnt signaling pathway - Zhigang Zhao; Xiaojing Zhu; Jinyuan Xu; Penglong Song; Yanan Sun; Zhenming Yang; Li Wang; Jiarui Zhang; Rui Zhao; Xiaoxue Chen; Wenjing Li; Linli Tian; et al. (Functional & Integrative Genomics, 2025)

Immobilization of arsenic and antimony by silica-Fe (hydr)oxides composite: investigation of potential ecological effects on the soil microbial environment - Rui Xu; Yaxin Tian; Qian Li; Guangfei Qu; Lang Liao; Zhe Yin; Zhenguo Wu; Yuqi Han; Yan Zhang; Yongbin Yang; Dongbin Liu; Haiyan Yan; et al. (Environmental Geochemistry and Health, 2025)

Unveiling Differences in Source Apportionment and Optical Properties of Wintertime Carbonaceous Aerosols in Northern and Southern Chinese Cities - Rui Li; Qiyuan Wang; Jie Tian; Yong Zhang; TingTing Wu; Lu Qi; Yang Chen; Shaofei Kong; Suixin Liu; Jin Wang; Julian Shi; Yuemei Han; et al. (Aerosol Science and Engineering, 2025)

Enhanced electrocatalytic oxidation of high-salinity quaternary ammonium compound wastewater using CNTs-(Ru Ir O2)/Ti Anode - Hao-Tian Liu; Han-Qing Zhao; Yi-Rui Yang; Shuang Wu; Jia-Ping Huang; Rui-Han Yu; Hongcheng Bai; Aqiang Ding; Daijun Zhang; Peili Lu (Journal of Environmental Sciences, 2025)

Effect of radio frequency heating on structure and physicochemical properties of protein and starch based on gelatinization degree of rice flour - Dongsheng Hu; Gaoji Yang; Yingqi Tian; Mengge Li; Liumin Fan; Rui Li; Shaojin Wang (Food Research International, 2025)

Surface oxygen vacancies and their synergy effect with Pt in Pt/CoCeOx promoting H2 activation for furfural hydrogenation - Yu Fang; Rui Wang; Min Tian; Shanyu Yi; Luna Ruan; Xin Duan; Huan Zhang; Zhiqing Yang; Hengqiang Ye; Lihua Zhu (Chemical Engineering Journal, 2025)

Nitrogen-oxygen radical generator-mediated in situ activation of live-cell prodrug for rational combination therapy - Ting Hou; Zi-Tao Shen; Wan-Ting Chen; Yang Song; Yin-Yu Yan; Zi-Jiang Luo; You-Yang Li; Yu-Ting Shan; Rui-Cheng Li; Tian-Yu Shen; Jia-Qin Long; Li Yin; et al. (Chemical Engineering Journal, 2025)

Differences in the home-field effects of litter decomposition modulate changes in soil microbial nutrient limitations: insights from eco-enzyme stoichiometry - Yongxia Meng; Peng Li; Lie Xiao; Jialiang Liu; Chaoya Zhang; Shutong Yang; Xiaoming Zhang; Yunqi Wang; Tian Wang; Rui Wang (CATENA, 2025)

Dynamics of lignocellulose degradation by acid: Kinetic insights into high-solid acid pretreatment at normal temperatures - Qianqian Yang; Rui Zhai; Yihang Tian; Mingjie Jin (Bioresource Technology, 2025)

Effect of primate protection on threatened and endemic vertebrates, plants, ecosystem services, and future climate refugia - Yin Yang; Chen Li; Yi‐Hao Fang; Guo‐Peng Ren; Zhi‐Pang Huang; Yan‐Peng Li; Liang‐Wei Cui; Meng‐Ran Chu‐yuan; Colin A. Chapmman; Cyril C. Grueter; Jian Zhou; Wen‐Bo Yan; et al. (Conservation Biology, 2025)
Primates, 69% of which are threatened with extinction, are the third most specious order of mammals. We used primates as model taxa to examine the umbrella effects of primates on ecosystem services and the protection of other vertebrates and seed plants in Yunnan Province, China. We identified areas of conservation priority for 16 primate species and determined which other threatened and endemic terrestrial vertebrates and seed plants would be protected through a program targeting primate conservation. Areas of high primate species richness were spatially correlated with the distribution of 601 species of threatened and endemic vertebrates and 4010 seed plants. Primate species richness was positively correlated with carbon sequestration and enhanced water and soil conservation and coincided with future areas of climate refugia. If 30% of Yunnan's land area were designated as primate conservation priority areas, then 52.3% of the province's average annual carbon sequestration, 51.7% of its water conservation, 54.1% of its soil retention, and 30‐33% of its climate‐stable areas would be protected. Protecting primates as umbrella taxa uniquely contributes to maintaining biodiversity and ecosystem services that promote ecosystem stability. Although we focused on a single mammalian order in a single region, our approach for umbrella taxa evaluation has broad applicability and can help achieve multiple conservation targets of the Kunming–Montreal Global Biodiversity Framework.

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Perfluorooctane sulfonate exposure disrupts steroid hormone synthesis in rats via the gut-metabolism-testis axis - Weizhen Hua; Rui Yang; Md Nur Alam; Zhenbin Che; Wanqing Zhu; Meiping Tian; Yan-Yang Lu; Yan Sun; Qingyu Huang (Environmental Pollution, 2025)

Prediction and changing patterns of physicochemical properties of rice flour during radio frequency heating - Dongsheng Hu; Jiahong Yuan; Mengge Li; Yingqi Tian; Gaoji Yang; Liumin Fan; Rui Li; Shaojin Wang (Innovative Food Science & Emerging Technologies, 2025)

Females adapted better than males in Populus deltoides to simulated nitrogen deposition - Fang He; Shu-Ying Wei; Rui-Quan Wang; Jia Yao Tang; Peng Yang; Ting Wang; Jin-Liang Huang; Gang Chen; Tian-Tian Lin (Plant and Soil, 2025)

Insight into unloading and geostress characteristics of high slopes based on valley evolution: a case study in Luding county, China - Hongfu Zhou; Shuwu Li; Fan Yang; Tian Fang; Rui Li; Jingyi Xue; Jinpeng Hu; Jiang Xing (Bulletin of Engineering Geology and the Environment, 2025)

Estimation of Soil Organic Carbon Stocks Utilizing Machine Learning Algorithms and Multi-source Geospatial Data in Coastal Wetlands of Tianjin and Hebei, China - Rui Yang; Mingyue Liu; Yongbin Zhang; Weidong Man; Jingfen Tong; Dong Liu; Qingwen Zhang; Caiyao Kou; Xiang Li; Yahui Liu; Di Tian; Xuan Yin; et al. (Chinese Geographical Science, 2025)

Association between serum elementomics of 48 elements and female fecundity: evidence from a nested case-control study in China - Tian Tian; Fang Liu; Li Li; Jing Wei; Kailibinuer Kayimu; Yu Fu; Huahua Jiang; Fei Kong; Rui Yang; Yuanyuan Wang; Xiaoyu Long; Jie Qiao (International Journal of Hygiene and Environmental Health, 2025)

Impact of watershed-scale land restoration on soil microbial communities and their functions: Insights from metagenomic analysis - Rui Yang; Shaoqing Guo; Lijuan Huo; Gaiqiang Yang; Shuting Tian (Environmental Research, 2025)

Contrasting Effects of Warming and Nitrogen Addition on soil CO2 Emission in a Semi-Arid Grassland on the Loess Plateau of China - Mingfeng Jiang; Zhun Tian; Rui Wang; Zihan Sun; Yang Peng; Chao Fang (Water, Air, & Soil Pollution, 2025)

Salty tide enhanced ecotoxicological risk of trace metals in the lower reach of the Pearl River, China via altering their phase partitioning and chemical speciation - Lei Gao; Chao Yan; Chenchen Yang; Rui Li; Qirui Wu; Di Tian; Lei Ouyang (Journal of Hydrology, 2025)

Evolution of and mechanisms controlling water chemistry in the Beijiang River Basin over the past four decades - Zaizhi Yang; Tao Jiang; Zuobin Liang; Xinfeng Zhao; Kun Ren; Di Tian; Lei Gao; Qirui Wu; Shaoheng Li; Rui Li; Lichun Xie; Jianyao Chen (Journal of Geochemical Exploration, 2025)

Enhanced gut damage and microbial imbalance in bullfrog tadpoles (Lithobates catesbeiana) exposed to polystyrene microplastics under high-temperature conditions - Zhilong Wang; Jun Xie; Guangjun Wang; Huirong Yang; Zhifei Li; Kai Zhang; Rui Shu; Wenping Xie; Jingjing Tian; Hongyan Li; Wangbao Gong; Yun Xia (Environmental Pollution, 2025)

The recruitment of alkaline phosphatase-positive endogenous neural stem cells enables robust neurogenesis and neural pathways reconstruction following spinal cord injury - Rong-Jie Wu; Jia-Lin Liu; Zheng-Hong Chen; Jing Xu; Ying Ding; Hai-Yang Yu; Chuang-Ran Wu; Shang-Bin Yang; Rui Liu; Yi-Nan Guo; Yue Yang; Ting-Ting Wu; et al. (Chemical Engineering Journal, 2025)

Epigenetics in the modern era of crop improvements - Yan Xue; Xiaofeng Cao; Xiangsong Chen; Xian Deng; Xing Wang Deng; Yong Ding; Aiwu Dong; Cheng-Guo Duan; Xiaofeng Fang; Lei Gong; Zhizhong Gong; Xiaofeng Gu; et al. (Science China Life Sciences, 2025)
Epigenetic mechanisms are integral to plant growth, development, and adaptation to environmental stimuli. Over the past two decades, our comprehension of these complex regulatory processes has expanded remarkably, producing a substantial body of knowledge on both locus-specific mechanisms and genome-wide regulatory patterns. Studies initially grounded in the model plant Arabidopsis have been broadened to encompass a diverse array of crop species, revealing the multifaceted roles of epigenetics in physiological and agronomic traits. With recent technological advancements, epigenetic regulations at the single-cell level and at the large-scale population level are emerging as new focuses. This review offers an in-depth synthesis of the diverse epigenetic regulations, detailing the catalytic machinery and regulatory functions. It delves into the intricate interplay among various epigenetic elements and their collective influence on the modulation of crop traits. Furthermore, it examines recent breakthroughs in technologies for epigenetic modifications and their integration into strategies for crop improvement. The review underscores the transformative potential of epigenetic strategies in bolstering crop performance, advocating for the development of efficient tools to fully exploit the agricultural benefits of epigenetic insights.

Isotope tracer study of soil erosion in a typical sub-watershed in the eastern Tianshan Mountains, China - Ninglu Zhang; Jianjun Yang; Wenli Xing; Xinyu Liu; Feifei Sheng; Wanqing Zhao; Zhiguang Zhang; Ziqi Tian; Rui Chen (Journal of Environmental Radioactivity, 2025)

The tumor suppressor SALL2 opposes chemotherapeutic resistance in breast cancer - Qiji Li; Chenxin Li; Yuhao Zhang; Zihan Zheng; Yun Wang; Yingqian Yang; Qingqing Zhu; Rui Wang; Wanhui Xu; Chengming Zhu; Qin Tian; Meng Wang; et al. (Molecular and Cellular Biochemistry, 2025)

CORBES: Radiation belt survey with international small satellite constellation - Ji Wu; Li Deng; Jaan Praks; Marius Anger; Philipp Oleynik; Wojciech Hajdas; Jin-Dong Wang; Shen-Yi Zhang; Bin Zhou; Li Zeng; Jinbin Cao; David Fischer; et al. (Advances in Space Research, 2025)

Omics research in atherosclerosis - Kai-Jiang Tian; Yu Yang; Guo-Shuai Chen; Nian-hua Deng; Zhen Tian; Rui Bai; Fan Zhang; Zhi-Sheng Jiang (Molecular and Cellular Biochemistry, 2025)

Monsoon Climate and Anthropogenic Influences Shape Primate Distributions Across the Southeastern Edge of the Qinghai‐Tibet Plateau - Chen Li; Yi‐hao Fang; Guo‐peng Ren; Yan‐peng Li; Zhi‐pang Huang; Liang‐wei Cui; Dionisios Youlatos; Paul A. Garber; Xi‐jun Ni; Hua Zhu; De‐wen Luo; Xin Liu; et al. (Global Change Biology, 2025)
The southeastern edge of the Qinghai‐Tibet Plateau (Yunnan, China) exhibits high biodiversity but stark differences in species richness between its western Longitudinal Range Gorge (LRG) and eastern Yunnan Plateau (YP). We collected distribution data for 16 primate species in Yunnan and analyzed palynological records over the past 20 ka from 21 localities to identify the biogeographic, climatic, and anthropogenic factors that have driven the present‐day distribution of primates in this region. By integrating local ecological knowledge, field surveys, species distribution models, niche utilization rates, and historical vegetation and land use changes, we found that spatial–temporal shifts in the monsoon climate have been a critical factor in shaping primate species richness on the southeastern edge of the Qinghai‐Tibet Plateau. Compared to the YP, the LRG receives more precipitation, has more limited seasonal temperature variation, and has higher minimum temperatures during the coldest month. These conditions have facilitated the development of moist evergreen broadleaf forests, which represent a more suitable habitat for the 14 primate species that inhabit this area. In contrast, the drought‐adapted forests of the YP support only one primate species. Palynological records indicate that the differentiation of the LRG and YP predates human influence. However, over the past 2000 years, anthropogenic habitat loss and hunting have significantly affected the distribution of primates. The ranges of gibbons, langurs, and snub‐nosed monkeys are now restricted to the central and northern regions of the LRG and have disappeared from lower elevations. Lorises have disappeared from their northernmost range. In contrast, the distribution of macaques has remained relatively stable. The Yangtze‐Red River‐24° N line marks the biogeographic boundary of high primate species richness and biodiversity in the LRG and southeastern Yunnan. Our research suggests that changes in monsoon climate have fundamentally shaped contemporary species richness, while recent anthropogenic pressures have caused ‘range contraction’ for many taxa.

Specific cation effects on soil water infiltration and soil aggregate stability–Comparison study on variably and permanently charged soils - Shishu Yang; Rui Tian; Haiyang Wang; Yekun Zhang; Hang Li (Soil and Tillage Research, 2025)

A novel framework for river organic carbon retrieval through satellite data and machine learning - Shang Tian; Anmeng Sha; Yingzhong Luo; Yutian Ke; Robert Spencer; Xie Hu; Munan Ning; Yi Zhao; Rui Deng; Yang Gao; Yong Liu; Dongfeng Li (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Phases partitioning and occurrence forms of arsenic, chromium, and vanadium in a tidal reach of the Pearl river estuary, South China - Lei Gao; Chao Yan; Chenchen Yang; Rui Li; Qirui Wu; Di Tian; Lei Ouyang (Environmental Pollution, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Screening heat-resistant energetic molecules via deep learning and high-throughput computation - Jian Liu; Jie Tian; Rui Liu; Yuechuan Tang; Chunming Yang; Junhong Zhou; Chaoyang Zhang (Chemical Engineering Journal, 2025)

Experiment and Peridynamics Simulation on Failure Mechanical Behavior of Cylindrical Sandstone Containing Two Persisting Fissures Under Conventional Triaxial Compression - Sheng-Qi Yang; Heng Li; Shi-Gui Du; Rui Yong; Su-Sheng Wang; Wen-Ling Tian; Yun-Jin Hu; Yong Niu (Rock Mechanics and Rock Engineering, 2025)

Taloring sawdust derived hydrochar via red mud for cadmium removal: Electron transfer insight and recyclability assessment - Ting Cui; Dingxiang Chen; Ran Duan; Fan Yang; Danting Li; Lin Tian; Yong Zhang; Huabin Wang; Rui Xu (Chemosphere, 2025)

Improvement of ecological structure and function in phosphorus tailings-based soils through phosphorus-solubilizing bacteria inoculation and magnetic field treatment - Caiyue Jin; Xinxin Liu; Bangjin Chen; Guangfei Qu; Yaxin Tian; Fenghui Wu; Jieqian Yang; Rui Xu; Ping Ning (Journal of Environmental Chemical Engineering, 2025)

Radio frequency inactivation of Bacillus cereus and natural microbiota in brown rice: Evaluation of inactivation kinetics and germination capacity - Gaoji Yang; Dingting Zhou; Juanjuan Xu; Yingqi Tian; Rui Li; Shaojin Wang (Food Control, 2025)

Reversibility of polystyrene nanoplastics-induced disruption of testosterone biosynthesis in mice: The role of histone modifications - Yan-Yang Lu; Rui Yang; Meiyi Cao; Lu Lu; Wanqing Zhu; Weizhen Hua; Meiping Tian; Yan Sun; Qingyu Huang (Environmental Pollution, 2025)

Sleep deprivation stimulates adaptive thermogenesis by activating AMPK pathway in mice - Tian-Shu Zheng; Xin-Ran Gao; Rui-Ping Xu; Yi-Fei Zhao; Zhi-Teng Yang; De-Hua Wang (Journal of Comparative Physiology B, 2025)

An effective strategy for high-value utilization of chromite ore processing residue (COPR) through reductive alkali roasting and physical separation - Cheng Tian; Cunfang Lu; Jun Yang; Rui Xu; Min Zhang; Juan Wen; Yelei Wang; Shuo Zhang; Yuanyuan He; Dan Luo; Huazheng Luo; Xingran Zhang (Process Safety and Environmental Protection, 2025)

Readily recyclable, degradable, stretchable, highly conductive, anti-freezing and anti-drying glycerohydrogel for triboelectric nanogenerator - Sihan Jiang; Yang Wang; Meiqin Tian; Haiyang Zhang; Rui Wang; Haokun Yan; Hao Tan; Rasoul Esmaeely Neisiany; Wei Sun; Zhengwei You (Chemical Engineering Journal, 2025)

A combined strategy of brain neuroprotection and endogenous neuroregeneration for enhanced intracerebral hemorrhage treatment via an injectable biomimetic hydrogel with efficient ROS scavenging and therapeutics delivery - Jiake Xu; Luyao Wan; Xueqi Wang; Yang Wei; Yinhai He; Shenglan You; Rui Zhong; Chengwei Wang; Hao Li; Chao You; Meng Tian (Chemical Engineering Journal, 2025)

Therapeutic Potential of Mesenchymal Stem Cell-Derived Exosomes in Spinal Cord Injury - Jing An; Bo Chen; Rui Zhang; Ding Tian; Kuohao Shi; Lingling Zhang; Gaorong Zhang; Jingchao Wang; Hao Yang (Molecular Neurobiology, 2025)

Prediction of available energy and amino acid digestibility in the Chinese paddy rice fed to growing pigs - Rui Li; Ganyi Feng; Qing Ouyang; Xianji Jiang; Gang Yang; Xiaojie Liu; Hui Tang; Mingzhou Tian; Qiang Xiang; Menglong Deng; Cimin Long; Ruilin Huang (Animal Feed Science and Technology, 2025)

Higher water content observed in smaller size fraction of Chang'e-5 lunar regolith samples - Honglei Lin; Rui Xu; Shuai Li; Rui Chang; Hejiu Hui; Yang Liu; Hengci Tian; Kai Fan; Zhiping He; Huaiyu He; Wei Yang; Yangting Lin; et al. (Science Bulletin, 2024)

Contrasting fracturing and cementation timings during shale gas accumulation and preservation: An example from the Wufeng-Longmaxi shales in the Fuling shale gas field, Sichuan Basin, China - Tao Luo; Xiaowen Guo; Zhiliang He; Jian-xin Zhao; Ze Tao; Tian Dong; Rui Yang; Junlin Chen (Marine and Petroleum Geology, 2024)

The role of probiotics in the treatment of non-alcoholic fatty liver disease (NAFLD): New insights based on meta-analysis and subgroup analysis - Rui Xiao; Yang Cao; Linlin Wang; Peijun Tian; Qixiao Zhai; Jianxin Zhao; Gang Wang; Yu Zhu (Food Bioscience, 2024)

Elevating electrochemical performance of Na4MnCr(PO4)3 cathode material for sodium ion batteries through the synergistic effect of Sc doping and RuO2/C coating - Qing Zhu; Jinxin Wu; Rui Tong; Xiuli Hu; Ningchen Tian; Botian Liu; Jiqiong Jiang; Yanwei Li; Jianwen Yang; Jianwei Zhao (Chemical Engineering Journal, 2024)

Hybrid packed bed bioreactor using combined biodegradation and ozonation to enhance nitrogen and micropollutants removal from landfill leachate - Xuetong Yang; Ze Liu; Changtao Chen; Tao Zhang; Qintong Wang; Rui Zhang; Feng Duan; Xiang Tian; Mingshui Yao; Kristof Demeestere; Stijn W.H. Van Hulle (Bioresource Technology, 2024)

Probiotic nucleotides increase IL-10 expression in airway macrophages to mitigate airway allergy - Jinmei Xue; Zhizhen Liu; Bailing Xie; Rui Dong; Juan Wu; Yisha Wu; Zhihan Xu; Yuhe Tian; Yao Wei; Zhigang Geng; Lei Lu; Yu Liu; et al. (Inflammation Research, 2024)

Genesis of high-Al chromitites from Xiaosuihe peridotite (Central Jilin Province, NE China): Implication for initial subduction of the Paleo-Asian ocean - Bing-Qian Ding; Fu-Ping Pei; Jing-Yang Wei; Jin-Rui Zhang; Zi-Cheng Guan; Kai Song; Tian-Jiao Sang; Peng-Yi Li (Lithos, 2024)

Polystyrene shell-based “coconut-like” and “pomegranate-like” microencapsulated phase change materials: Formation mechanism, thermal conductivity/stability enhancement and their application in thermal management - Wei Zhang; Rui Pan; Jihua Yang; Mengru Liu; Yunle Yao; Awang Zhang; Yi Gong; Zhengya Gan; Rui Hu; Jianjun Ding; Lin Chen; Xian Zhang; et al. (Chemical Engineering Journal, 2024)

A Cysteinyl-tRNA Synthetase Mutation Causes Novel Autosomal-Dominant Inheritance of a Parkinsonism/Spinocerebellar-Ataxia Complex - Han-Kui Liu; Hong-Lin Hao; Hui You; Feng Feng; Xiu-Hong Qi; Xiao-Yan Huang; Bo Hou; Chang-Geng Tian; Han Wang; Huan-Ming Yang; Jian Wang; Rui Wu; et al. (Neuroscience Bulletin, 2024)
This study aimed to identify possible pathogenic genes in a 90-member family with a rare combination of multiple neurodegenerative disease phenotypes, which has not been depicted by the known neurodegenerative disease. We performed physical and neurological examinations with International Rating Scales to assess signs of ataxia, Parkinsonism, and cognitive function, as well as brain magnetic resonance imaging scans with seven sequences. We searched for co-segregations of abnormal repeat-expansion loci, pathogenic variants in known spinocerebellar ataxia-related genes, and novel rare mutations via whole-genome sequencing and linkage analysis. A rare co-segregating missense mutation in the CARS gene was validated by Sanger sequencing and the aminoacylation activity of mutant CARS was measured by spectrophotometric assay. This pedigree presented novel late-onset core characteristics including cerebellar ataxia, Parkinsonism, and pyramidal signs in all nine affected members. Brain magnetic resonance imaging showed cerebellar/pons atrophy, pontine-midline linear hyperintensity, decreased rCBF in the bilateral basal ganglia and cerebellar dentate nucleus, and hypo-intensities of the cerebellar dentate nuclei, basal ganglia, mesencephalic red nuclei, and substantia nigra, all of which suggested neurodegeneration. Whole-genome sequencing identified a novel pathogenic heterozygous mutation (E795V) in the CARS gene, meanwhile, exhibited none of the known repeat-expansions or point mutations in pathogenic genes. Remarkably, this CARS mutation causes a 20% decrease in aminoacylation activity to charge tRNA Cys with L-cysteine in protein synthesis compared with that of the wild type. All family members carrying a heterozygous mutation CARS (E795V) had the same clinical manifestations and neuropathological changes of Parkinsonism and spinocerebellar-ataxia. These findings identify novel pathogenesis of Parkinsonism-spinocerebellar ataxia and provide insights into its genetic architecture.

Soil urease functional stability to Hg pollution: An ecotoxicological perspective - Hui Huang; Haixia Tian; Yan Li; Ziquan Wang; Tiantian Yang; Rui Qian; Mallavarapu Megharaj; Wenxiang He (Ecotoxicology, 2024)

Propane dehydrogenation performance of titanosilicate-1 supported CoOx catalysts by adjusting the acidity and reducibility - Xue Cai; Yongzheng Zhao; Lili Cai; Xiaoyan Tian; Cunzi Wei; Dandan Qin; Meitong Li; Rui Tao; Wenling Chu; Weishen Yang (Fuel, 2024)

Bifunctional halloysite nanotube-based Ripk1 siRNA delivery system rescues cognitive impairment by targeting amyloid β plaques for clearance and reducing necrotic neurons in Alzheimer’s disease mice - Linmei Wu; Shuo Tan; Yizhu Yan; Lianghao Zhu; Zhaoyuan Wu; Zhihong Liu; Qiang Cheng; Qiuhao Qu; Xinyu Li; Qi Zhang; Jiayi Liu; Jun Chang; et al. (Chemical Engineering Journal, 2024)

Activation AMPK in Hypothalamic Paraventricular Nucleus Improves Renovascular Hypertension Through ERK1/2-NF-κB Pathway - Li-Yan Fu; Yu Yang; Rui-Juan Li; Abdoulaye Issotina Zibrila; Hua Tian; Xiu-Yue Jia; Jin-An Qiao; Jin-Min Wu; Jie Qi; Xiao-Jing Yu; Yu-Ming Kang (Cardiovascular Toxicology, 2024)

Engineering disease-resistant plants with alternative translation efficiency by switching uORF types through CRISPR - Jingjing Tian; Zhijuan Tang; Ruixia Niu; Yulu Zhou; Dan Yang; Dan Chen; Ming Luo; Rui Mou; Meng Yuan; Guoyong Xu (Science China Life Sciences, 2024)

A highly sensitive and colorimetric fluorescent probe for visualizing hydroxylamine in immune cells - Wei Du; Yang Tian; Yu-An Feng; Xiao-Wei Cong; Rui Tan; Ya-Wen Wang; Yu Peng (Analytica Chimica Acta, 2024)

Micronutrient perspective on COVID-19: Umbrella review and reanalysis of meta-analyses - Yafei Xie; Jianguo Xu; Dan Zhou; Mingyue Guo; Mengxiang Zhang; Ya Gao; Ming Liu; Jiyuan Shi; Kelu Yang; Qingyong Zheng; Liang Zhao; Yu Qin; et al. (Critical Reviews in Food Science and Nutrition, 2024)

Structurally diverse 1,2-diarylpropanes from the fruit of Crataegus pinnatifida and the investigation on their mirror-image ECD spectra with the same absolute configurations - Tian-Ming Lv; Rui Guo; Bo-Han Yang; Peng Zhao; Bin Lin; Xiao-Xiao Huang; Shao-Jiang Song (Phytochemistry, 2024)

Comparative steroidogenic effects of hexafluoropropylene oxide trimer acid (HFPO-TA) and perfluorooctanoic acid (PFOA): Regulation of histone modifications - Fuping Li; Rui Yang; Lu Lu; Weizhen Hua; Yan Sun; Meiping Tian; Yanyang Lu; Qingyu Huang (Environmental Pollution, 2024)

Stretchable ionogels: Recent advances in design, toughening mechanisms, material properties and wearable devices applications - Caiyue Huang; Xiaohua Jia; Ding Wang; Xisheng Sun; Qi Liang; Rui Tian; Liyuan Guo; Jin Yang; Haojie Song (Chemical Engineering Journal, 2024)

Experimental study and model optimization of thermodynamic performance of a single screw water vapor compressor - Huafu Zhang; Zhentao Zhang; Lige Tong; Junling Yang; Yanan Li; Li Wang; Xia Guo; Rui Tian; Mingxin He; Chongguang Gao (International Journal of Refrigeration, 2024)

Arbuscular mycorrhizal fungi reduce ammonia emissions under different land-use types in agro-pastoral areas - Huaisong WANG; Rui GUO; Yibo TIAN; Nan CUI; Xinxin WANG; Lei WANG; Zhongbao YANG; Shuying LI; Jixun GUO; Lianxuan SHI; Tao ZHANG (Pedosphere, 2024)

Enhanced tough recyclable hemiaminal dynamic covalent network with boron nitride composites material with high thermal conductivity at low filler content - Caiyue Huang; Xiaohua Jia; Rui Tian; Jin Yang; Haojie Song (Journal of Cleaner Production, 2024)

Fly ash-dominated High-Strength Engineered/Strain-Hardening Geopolymer Composites (HS-EGC/SHGC): Influence of alkalinity and environmental assessment - Jian-Cong Lao; Rui-Yang Ma; Ling-Yu Xu; Yang Li; Yi-Nong Shen; Jie Yao; Yan-Shuai Wang; Tian-Yu Xie; Bo-Tao Huang (Journal of Cleaner Production, 2024)

Submicron spatial resolution Pb-Pb dating for the formation age of Chang'e-5 basalt - Jia-Long Hao; Wei Yang; Hui-Cun He; Di Zhang; Sen Hu; Heng-Ci Tian; Rui-Ying Li; Yang-Ting Lin (Lithos, 2024)

Covalent-Metal organic Frameworks: Preparation and applications - Zhaobo Wang; Chen Wang; Qiming Hu; Xuefei Lei; Rui Guo; Junhua You; Ye Tian; Fan Yang; Meili Lv (Chemical Engineering Journal, 2024)

Long-term MNNG exposure promotes gastric carcinogenesis by activating METTL3/m6A/miR1184 axis-mediated epithelial-mesenchymal transition - Tong Liu; Yan-lu Feng; Rui-ying Wang; Sheng Yang; Yi-ling Ge; Tian-yi Zhang; Jie Li; Cheng-yun Li; Ye Ruan; Bin Luo; Ge-yu Liang (Science of The Total Environment, 2024)

Estimation of water quality variables based on machine learning model and cluster analysis-based empirical model using multi-source remote sensing data in inland reservoirs, South China - Di Tian; Xinfeng Zhao; Lei Gao; Zuobing Liang; Zaizhi Yang; Pengcheng Zhang; Qirui Wu; Kun Ren; Rui Li; Chenchen Yang; Shaoheng Li; Meng Wang; et al. (Environmental Pollution, 2024)

Revealing the membrane fouling behavior and interfacial interaction mechanism in a combined visible light photocatalysis-ultrafiltration system for advanced purification of NOM - Rui Yu; Yanling Yang; Liping Tian; Xing Li; Chunjiao Liu; Tianjie Sun; Haiqing Chang; Zhiwei Zhou (Journal of Water Process Engineering, 2024)

LED-driven photocatalytic degradation of tetracycline by chromite ore processing residue (COPR): Mechanism, pathway, toxicity assessment - Shuo Zhang; Cunfang Lu; Yelei Wang; Cheng Tian; Peng Chen; Mingyuan Yang; Min Zhang; Rui Xu; Yuanyuan He; Zilong Li (Journal of Cleaner Production, 2024)

Fluid evolution and gas enrichment in the Wufeng-Longmaxi shale reservoirs of the eastern Sichuan Basin, SW China - Tao Luo; Xiaowen Guo; Zhiliang He; Tian Dong; Ze Tao; Rui Yang; Keqing Wang (Journal of Asian Earth Sciences, 2024)

Fermentation characteristics and prebiotic potential of enzymatically synthesized butyryl-fructooligosaccharides - Zixin Yang; Diming Tan; Weiwen Chen; Jun Hu; Rui Huang; Xiyang Wu; Milen I. Georgiev; Weibin Bai; Lingmin Tian (Carbohydrate Polymers, 2024)

Utilization of halophytes in saline agriculture and restoration of contaminated salinized soils from genes to ecosystem: Suaeda salsa as an example - Chen Yang Li; Rui He; Chang Yan Tian; Jie Song (Marine Pollution Bulletin, 2023)

The co-regulation of the gut microbiome and host genes might play essential roles in metformin gastrointestinal intolerance - Huixiang Zhang; Jiao Lai; Lihuan Zhang; Wei Zhang; Xun Liu; Qilin Gong; Hongxi Tian; Mingzhi Yang; Tao Yang; Rui Zhao; Dongqing Li; Hehua Huang; et al. (Toxicology and Applied Pharmacology, 2023)

Synergistic effect triggered by Fe2O3 and oxygen-induced hydroxyl radical enhances formation of amino-phenolic humic-like substance - Yingchao Zhang; Zhitao Bi; Wenxin Tian; Zhenyu Ge; Yang Xu; Rui Xu; Hongqiong Zhang; Shoufeng Tang (Journal of Environmental Management, 2023)

Physicochemical stability of lichenan (Usnea longissima) decorated-selenium nanoparticles for cancer chemoprevention - Ziying Yang; Yajie Hu; Panpan Yue; Rui Tian; Huiling Li; Baozhong Lü; Gegu Chen; Feng Peng (Food Bioscience, 2023)

An interval water demand prediction method to reduce uncertainty: A case study of Sichuan Province, China - Xinyu Xia; Bin Liu; Rui Tian; Zuli He; Suyue Han; Ke Pan; Jingjing Yang; Yiting Zhang (Environmental Research, 2023)

Quantitative Estimation on Methane Storage Capacity of Organic-Rich Shales from the Lower Silurian Longmaxi Formation in the Eastern Sichuan Basin, China - Xiaowen Guo; Tao Luo; Tian Dong; Rui Yang; Yuanjia Han; Jizheng Yi; Sheng He; Zhiguo Shu; Hanyong Bao (Journal of Earth Science, 2023)

Early clues and molecular mechanism involved in neurodegenerative diseases induced in immature mice by combined exposure to polypropylene microplastics and DEHP - Ge Yang; Cunyi Gong; Xinyue Zheng; Fei Hu; Jie Liu; Tian Wang; Xinyue Chen; Min Li; Zhihong Zhu; Ling Zhang; Rui Li (Environmental Pollution, 2023)

A new anchor-siphon drainage combined method used for slope stabilization - Hong-yue Sun; Xu Wang; Yang Yu; Jun-wei Shu; Tian-long Wang; Rui Luo; Zhao-wei Chu (Journal of Mountain Science, 2023)

Triterpenoid saponins from Psammosilene tunicoides and their antinociceptive activities - Yan-Hong Li; Xi-Shan Bai; Xiu-Xia Yang; Yu-Xiao Li; Hong-Rui Li; Zi-Liang Wang; Wei Wang; Kai Tian; Xiang-Zhong Huang (Phytochemistry, 2023)

A multilayer perceptron-based fast sunlight assessment for the conceptual design of residential neighborhoods under Chinese policy - Can Jiang; Xiong Liang; Yu-cheng Zhou; Yong Tian; Shengli Xu; Jia-Rui Lin; Zhiliang Ma; Shiji Yang; Hao Zhou (Building and Environment, 2023)

Effects of atrazine on microbial metabolic limitations in black soils: Evidence from enzyme stoichiometry - Tiancong Gao; Haixia Tian; Ziqi Wang; Jing Shi; Rui Yang; Fang Wang; Leilei Xiang; Yunchao Dai; Mallavarapu Megharaj; Wenxiang He (Chemosphere, 2023)

Farmers’ participation into the recovery of waste agricultural plastic film: An application of the Theory of Planned Behavior - Ze-Ying Zhao; Wen-Bo Li; Peng-Yang Wang; Hong-Yan Tao; Rui Zhou; Jin-Ying Cui; Jian Zhang; Tao Tian; Xu-Zhe Zhao; Yi-Bo Wang; You-Cai Xiong (Waste Management, 2023)

Nitrate attenuation with rising groundwater levels: An integrated assessment using isotope tracers and microbial signatures - Jie Li; Yulian Liu; Wei Dai; Jian Li; Pingheng Yang; Lijun Tian; Shihang Yu; Rui Zuo; Yuanzheng Zhai; Wei Song; Fan Yang; Ruijing Zhou; et al. (Journal of Hydrology, 2023)

Regeneration of high-performance materials for electrochemical energy storage from assorted solid waste: A review - Jia-feng Zhang; De-zhao Peng; Xiang-gang Gao; Jing-tian Zou; Long Ye; Guan-jun Ji; Bi Luo; Gui-hui Yu; Peng-fei Li; Xiao-wei Wang; Zao-wen Zhao; Bao Zhang; et al. (Journal of Cleaner Production, 2023)

Comprehensive understanding of tetracycline hydrochloride adsorption mechanism onto biochar-based gel pellets based on the combination of characterization-based and approximate site energy distribution methods - Bai-Qin Zhou; Qian-Qian Sang; Yu-Jun Wang; Hui Huang; Fang-Jun Wang; Rui-Chun Yang; Yuan-Tian Zhao; Zi-Jie Xiao; Chun-Yue Zhang; Hui-Ping Li (Journal of Cleaner Production, 2023)

Enzymatic synthesis of propionyl-fructooligosaccharides and their evaluation as a gut microbiota modulator - Diming Tan; Weiwen Chen; Zixin Yang; Minjing Rong; Rui Huang; Xiyang Wu; Weibin Bai; Lingmin Tian (Food Hydrocolloids, 2023)

Moringa oleifera Lam. leaves as new raw food material: A review of its nutritional composition, functional properties, and comprehensive application - Min Yang; Liang Tao; Xin-Rui Kang; Zi-Lin Wang; Ling-Yan Su; Ling-Fei Li; Fan Gu; Cun-Chao Zhao; Jun Sheng; Yang Tian (Trends in Food Science & Technology, 2023)

Corrigendum to “Efficient lead immobilization by bio-beads containing Pseudomonas rhodesiae and bone char” [J. Hazard. Mater. 447 (2023) 130772] - Junpeng Li; Rui Bai; Wei Chen; Chongyuan Ren; Fan Yang; Xiaochun Tian; Xiaofeng Xiao; Feng Zhao (Journal of Hazardous Materials, 2023)

AIWW: a new nutrition-screening tool for the oncologic population - Yi-Zhong Ge; Zhen-Ming Fu; Qi Zhang; Meng-Meng Song; Guo-Tian Ruan; Xi Zhang; Xiao-Wei Zhang; Xiang-Rui Li; Kang-Ping Zhang; Meng Tang; Xiao-Yue Liu; Ming Yang; et al. (Science China Life Sciences, 2023)

Selective CDK9 knockdown sensitizes TRAIL response by suppression of antiapoptotic factors and NF-kappaB pathway - Qian Yuan; Kui Su; Shuyi Li; Xinyi Long; Lang Liu; Jianwu Sun; Xin Yuan; Minghui Yang; Rui Tian; Wanting Zhang; Zhujie Deng; Quanjiang Li; et al. (Apoptosis, 2023)

The PIWI-specific insertion module helps load longer piRNAs for translational activation essential for male fertility - Xin Wang; Di-Hang Lin; Yue Yan; An-Hui Wang; Jiaoyang Liao; Qian Meng; Wen-Qing Yang; Heng Zuo; Min-Min Hua; Fengjuan Zhang; Hongwen Zhu; Hu Zhou; et al. (Science China Life Sciences, 2023)

Screening of goaty flavor-inhibiting lactic acid bacteria and their effects on the flavor profiles of goat milk cakes - Huaixiang Tian; Rui Yang; Xuefeng Sun; Haiyan Yu; Juan Huang; Haibin Yuan; Xinman Lou; Zhaohu Yuan; Chen Chen (Food Bioscience, 2023)

Experimental study on flow and heat transfer of supercritical carbon dioxide in zigzag channels with bending angle 30° for advanced nuclear systems - Sheng-hui Liu; Rui-long Liu; Yan-ping Huang; Xiao-liang Zhu; Liu Yang; Jia Tang; Bin Han; Tian-yang Xing; Xue-bin Zhao (Annals of Nuclear Energy, 2023)

Depositional-diagenetic process and their implications for pore development of Wufeng-Longmaxi shales in the Jiangdong block, Fuling shale gas field, SW China - Kefei Chen; Rui Yang; Hanyong Bao; Tian Dong; Aoqi Jia; Qinhong Hu; Xiaowen Guo; Sheng He (Marine and Petroleum Geology, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Efficient lead immobilization by bio-beads containing Pseudomonas rhodesiae and bone char - Junpeng Li; Rui Bai; Wei Chen; Chongyuan Ren; Fan Yang; Xiaochun Tian; Xiaofeng Xiao; Feng Zhao (Journal of Hazardous Materials, 2023)

Determination and prediction of digestible energy, metabolizable energy, and standardized ileal digestibility of amino acids in barley for growing pig - Rui Li; Mingzhou Tian; Ganyi Feng; Gaifeng Hou; Xianji Jiang; Gang Yang; Qiang Xiang; Xiaojie Liu; Cimi Long; Ruilin Huang; Yulong Yin (Animal Feed Science and Technology, 2023)

Low-cost mineral packing materials improve DOM and micropollutants removal from landfill leachate in ozonation bubble columns: Insights into the enhancement mechanisms and applicability of surrogate-based monitoring - Xuetong Yang; Changtao Chen; Tao Zhang; Xiang Tian; Rui Zhang; Dave Manhaeghe; Yunliang Zhao; Shaoxian Song; Kristof Demeestere; Stijn W.H. Van Hulle (Chemical Engineering Journal, 2023)

Rapid and massive fractionation of hemicelluloses for purifying cellulose at room temperature by tetramethylammonium hydroxide - Rui Tian; Bolang Zhu; Qiaoling Liu; Yajie Hu; Ziying Yang; Jun Rao; Yuying Wu; Baozhong Lü; Jing Bian; Feng Peng (Bioresource Technology, 2023)

Multi-index assessment of heavy metal contamination in surface sediments of the Pearl River estuary intertidal zone - Rui-Ze Liang; Yang-Guang Gu; Hai-Song Li; Yan-Jie Han; Jie Niu; Hong Su; Richard W. Jordan; Xiang-Tian Man; Shi-Jun Jiang (Marine Pollution Bulletin, 2023)

HIF-1α promotes paraquat induced acute lung injury and implicates a role NF-κB and Rac2 activity - Yong Zhu; Xiaoxiao Meng; Wenyu Yang; Jinfeng Wang; Jiaxiang Zhang; Rui Tian; Ruilan Wang; Qi Su; Wei Jin (Toxicology, 2023)

Janus fibrous membrane with directional liquid transport capacity for wound healing promotion - Haohong Pi; Yanli Xi; Jing Wu; Miaomiao Hu; Boyang Tian; Yiwen Yang; Rui Wang; Xiuqin Zhang (Chemical Engineering Journal, 2023)

Precise orbit determination for BDS-3 GEO satellites enhanced by intersatellite links - Xiaojie Li; Xiaogong Hu; Rui Guo; Chengpan Tang; Shuai Liu; Jie Xin; Jinglei Guo; Yijun Tian; Yufei Yang; Jianhua Yang; Xinglong Zhao (GPS Solutions, 2023)

Insight into mechanisms of heavy metal-induced natural clay aggregation - Qinyi Li; Rui Tian; Qingyuan Yang (Applied Clay Science, 2023)

Solar ring mission: Building a panorama of the Sun and inner-heliosphere - Yuming Wang; Xianyong Bai; Changyong Chen; Linjie Chen; Xin Cheng; Lei Deng; Linhua Deng; Yuanyong Deng; Li Feng; Tingyu Gou; Jingnan Guo; Yang Guo; et al. (Advances in Space Research, 2023)

Efficacy and Safety of Recombinant Human Prourokinase in Acute Ischemic Stroke: A Phase IIa Randomized Clinical Trial - Haiqing Song; Yuan Wang; Qingfeng Ma; Huisheng Chen; Bo Liu; Yi Yang; Jianguo Zhu; Shigang Zhao; Xiaoping Jin; Yongqiu Li; Yanyong Wang; Runxiu Zhu; et al. (Translational Stroke Research, 2022)

Enhancing extracellular electron transfer through selective enrichment of Geobacter with Fe@CN-modified carbon-based anode in microbial fuel cells - Xiao-Long Cheng; Qiang Xu; Qian-Wen Yang; Rui-Rui Tian; Biao Li; Su Yan; Xue-Ying Zhang; Jun Zhou; Xiao-Yu Yong (Environmental Science and Pollution Research, 2022)

Long non-coding RNA RPL34-AS1 ameliorates oxygen–glucose deprivation-induced neuronal injury via modulating miR-223–3p/IGF1R axis - Xin-ya Wei; Tian-qi Zhang; Rui Suo; You-yang Qu; Yan Chen; Yu-lan Zhu (Human Cell, 2022)

Impact of climate change on long-term variations of small yellow croaker (Larimichthys polyactis) winter fishing grounds - Rui Zhang; Yang Liu; Hao Tian; Shuhao Liu; Kaiwei Zu; Xinmei Xia (Frontiers in Marine Science, 2022)
Small yellow croaker ( Larimichthys polyactis ) is one of the key demersal species with high economic values and wide distribution in the China Seas. In this study, a Winter Fishing ground Abundance Index (WFAI) was developed by using fisheries survey data in 1971–1982 and used as the response variable to investigate the impacts of environmental variables, including surface current velocity (SCV), sea surface salinity (SSS), sea surface temperature (SST), and depth (DE). A total of 45 combinatorial generalized additive models (GAMs), generalized linear models (GLMs), and random forest models (RFs) were used to select the optimal WFAI prediction. The final WFAI distribution results showed that the winter fishing ground hotspots of small yellow croaker were mainly distributed between 11°C and 16°C isotherms and between 50-m and 100-m isobaths, and the area of winter fishing ground hotspots (WFHA) significantly decreased and the hotspots tended to move northward over the past 50 years. The shape of hotspots was strongly affected by temperature fronts and salinity fronts. Analysis with the climate indices revealed that the Atlantic Multidecadal Oscillation (AMO) might have a large influence on the distribution of small yellow croaker by affecting SST and SSS in the China Seas more than the Pacific Decadal Oscillation (PDO), North Pacific Gyre Oscillation (NPGO), and Arctic Oscillation Index (AOI). The future prediction based on two extreme scenarios (RCP2.6 and RCP8.5) indicated that the hotspots would obviously move northward. These findings will serve effectively the fishery resources monitoring, management, and evaluation of small yellow croaker in the China Seas.

Detection and typing of dengue virus by one-step RT-PCR-based high-resolution melting assay - Rui Tian; Hao Yan; Yang Jiang; Aiping Wu; Ling Li; Zhangnv Yang; Kuangming Yu (Virus Genes, 2022)

Extracellular vesicles derived from human Sertoli cells: characterizations, proteomic analysis, and miRNA profiling - Xiao-Hui Tan; Sheng-Ji Gu; Wen-Jie Tian; Wen-Peng Song; Yang-Yang Gu; Yi-Ming Yuan; Xue-Song Li; Zhong-Cheng Xin; Sae Woong Kim; Rui-Li Guan; Woong Jin Bae (Molecular Biology Reports, 2022)

The interplay of particle properties and solution chemistry on aggregation kinetics of soil nanoparticles - Ning Hu; Chen-yang Xu; Zeng-chao Geng; Fei-nan Hu; Qi-rui Li; Ren-tian Ma; Qiang Wang (Journal of Soils and Sediments, 2022)

In vitro Scolicidal Efficacy of 5-Fluorouracil and Radiation Against Protoscoleces of Echinococcus granulosus Sensu Lato - Pengfei Lu; Jun Li; Rui Mao; Hongzhi Qi; Liping Yang; Qin Zhou; Mengxiao Tian; Wenbao Zhang; Yongxing Bao (Acta Parasitologica, 2022)

Toxic encephalopathy induced by radix Sophorae tonkinensis - Xue-Lin Li; Hao-Tian Zhao; Jinming Han; Zhong-Rui Yan; Hai-Yang Wang (Acta Neurologica Belgica, 2022)

Chrysomutanin and related meroterpenoids from a DES mutant of the marine-derived fungus Penicillium chrysogenum S-3-25 - Hua Qiao; Shu-Hua Zhang; Yuan Dong; Yu Yang; Rui Xu; Bo Chen; Yi Wang; Tian-Jiao Zhu; Cheng-Bin Cui; Guo-Gang Zhang; Chang-Wei Li (Natural Product Research, 2022)

Dysfunction of FadA‐cAMP signalling decreases Aspergillus flavus resistance to antimicrobial natural preservative Perillaldehyde and AFB1 biosynthesis - Kunlong Yang; Qingru Geng; Yue Luo; Rui Xie; Tongzheng Sun; Zhen Wang; Ling Qin; Wei Zhao; Man Liu; Yongxin Li; Jun Tian (Environmental Microbiology, 2022)
Summary Aspergillus flavus is an opportunistic fungal pathogen that colonizes agriculture crops with aflatoxin contamination. We found that Perillaldehyde (PAE) effectively inhibited A . flavus viability and aflatoxin production by inducing excess reactive oxygen species (ROS). Transcriptome analysis indicated that the Gα protein FadA was significantly induced by PAE. Functional characterization of FadA showed it is important for asexual development and aflatoxin biosynthesis by regulation of cAMP‐PKA signalling. The Δ fadA mutant was more sensitive to PAE, while Δ pdeL and Δ pdeH mutants can tolerate excess PAE compared to wild‐type A . flavus . Further RNA‐sequence analysis showed that fadA was important for expression of genes involved in oxidation–reduction and cellular metabolism. The flow cytometry and fluorescence microscopy demonstrated that Δ fadA accumulated more concentration of ROS in cells, and the transcriptome data indicated that genes involved in ROS scavenging were downregulated in Δ fadA mutant. We further found that FadA participated in regulating response to extracellular environmental stresses by increasing phosphorylation levels of MAPK Kinase Slt2 and Hog1. Overall, our results indicated that FadA signalling engages in mycotoxin production and A . flavus resistance to antimicrobial PAE, which provide valuable information for controlling this fungus and AF biosynthesis in pre‐ and postharvest of agricultural crops.

Secondary metabolites isolated from Agrimonia pilosa Ledeb. - Hong-Rui Li; Yu-Kui Li; Jian Xiao; Cui Yang; Meng-Yuan Jiang; Kai Tian; Wei Wang; Yan-Hong Li; Xiang-Zhong Huang (Natural Product Research, 2022)

lncRNA SNHG16 Mediates Cell Proliferation and Apoptosis in Cholangiocarcinoma by Directly Targeting miR-146a-5p/GATA6 Axis - Tao Wu; Ming-Sheng Lei; Xu-Zhao Gao; Ting-Gang Xiong; Kang Yang; Qian Gong; Rui Tang; Yue-Peng Tian; Xiao-Hua Fu (Biochemical Genetics, 2021)

Genetic control of Fusarium head blight resistance in two Yangmai 158-derived recombinant inbred line populations - Haisheng Yan; Guoqiang Li; Jinxing Shi; ShunShun Tian; Xiaoqiu Zhang; Rui Cheng; Xin Wang; Yang Yuan; Shouyang Cao; Jiyang Zhou; Zhongxin Kong; Haiyan Jia; et al. (Theoretical and Applied Genetics, 2021)

A functional chromogen gene C from wild rice is involved in a different anthocyanin biosynthesis pathway in indica and japonica - Weihua Qiao; Yanyan Wang; Rui Xu; Ziyi Yang; Yan Sun; Long Su; Lizhen Zhang; Junrui Wang; Jingfen Huang; Xiaoming Zheng; Shijia Liu; Yunlu Tian; et al. (Theoretical and Applied Genetics, 2021)

Optimizing Protein-Glutaminase Expression in Bacillus subtilis - Xiaoying Ouyang; Yingjie Liu; Ruidan Qu; Min Tian; Ting Yang; Rui Zhu; Hongliang Gao; Mingfei Jin; Jing Huang (Current Microbiology, 2021)

Small RNA Sequencing Analysis of Germinating Single-bud Seedcane Sett in Sugarcane - Kai-Chao Wu; Lin Xu; Zhi-Nian Deng; Tian Pang; Rong-Hua Zhang; Yi-Jie Li; Xiao-Yan Liu; Cheng-Feng Huang; Wen-Xian Qin; Jian-Feng Wei; Li-Ping Wei; Yang-Rui Li; et al. (Sugar Tech, 2021)

Astrocyte-Derived Lactate Modulates the Passive Coping Response to Behavioral Challenge in Male Mice - Ya-Nan Yin; Jian Hu; Yi-Li Wei; Ze-Lin Li; Zhou-Cai Luo; Rui-Qi Wang; Ke-Xin Yang; Shu-Ji Li; Xiao-Wen Li; Jian-Ming Yang; Tian-Ming Gao (Neuroscience Bulletin, 2021)

High expression of long non-coding RNA Linc-A associates with poor survival in patients with colorectal cancer - Chong Zhao; Can Gan; Yang Xiao; Rui Liu; Linhao Zhang; Tian Lan; Yanting Ye; Huan Tong; Zhiyin Huang; Chengwei Tang; Jinhang Gao (Molecular Biology Reports, 2020)

Critical transition of soil bacterial diversity and composition triggered by nitrogen enrichment - Weixing Liu; Lin Jiang; Sen Yang; Zhou Wang; Rui Tian; Ziyang Peng; Yongliang Chen; Xingxu Zhang; Jialiang Kuang; Ning Ling; Shaopeng Wang; Lingli Liu (Ecology, 2020)
Soil bacterial communities are pivotal in regulating terrestrial biogeochemical cycles and ecosystem functions. The increase in global nitrogen (N) deposition has impacted various aspects of terrestrial ecosystems, but we still have a rudimentary understanding of whether there is a threshold for N input level beyond which soil bacterial communities will experience critical transitions. Using high‐throughput sequencing of the 16S rRNA gene, we examined soil bacterial responses to a long‐term (13 yr), multi‐level, N addition experiment in a temperate steppe of northern China. We found that plant diversity decreased in a linear fashion with increasing N addition. However, bacterial diversity responded nonlinearly to N addition, such that it was unaffected by N input below 16 g N·m −2 ·yr −1 , but decreased substantially when N input exceeded 32 g N·m −2 ·yr −1 . A meta‐analysis across four N addition experiments in the same study region further confirmed this nonlinear response of bacterial diversity to N inputs. Substantial changes in soil bacterial community structure also occurred between N input levels of 16 to 32 g N·m −2 ·yr −1 . Further analysis revealed that the loss of soil bacterial diversity was primarily attributed to the reduction in soil pH, whereas changes in soil bacterial community were driven by the combination of increased N availability, reduced soil pH, and changes in plant community structure. In addition, we found that N addition shifted bacterial communities toward more putatively copiotrophic taxa. Overall, our study identified a threshold of N input level for bacterial diversity and community composition. The nonlinear response of bacterial diversity to N input observed in our study indicates that although bacterial communities are resistant to low levels of N input, further increase in N input could trigger a critical transition, shifting bacterial communities to a low‐diversity state.

Assessment of genetic diversity in Camellia oleifera Abel. accessions using inter-simple sequence repeat (ISSR) and start codon targeted (SCoT) polymorphic markers - Pu Xiao; Huhu Liu; Dongping Wang; Wenyan Tang; Hui Yang; Chong Wang; Zhilong He; Rui Wang; Xiangnan Wang; Xiangyang Lu; Yongzhong Chen; Yun Tian (Genetic Resources and Crop Evolution, 2020)

Sulfur content in coal formed during different geologic periods in the Guangxi Province and the relationship with the depositional environment - Bohui Xu; Yuxin Song; Yuan Tian; Rui Yang; Fei Xu; Shuli Ding; Pengfei Sun (Arabian Journal of Geosciences, 2020)

The stability and pressure behavior characteristics of a special L-type face end formed by low-pressure mining technology without pre-driving roadway - Ya-jun Wang; Jun Yang; Man-chao He; Rui-feng Huang; Xi-chun Tian; Jian-ning Liu; Hao-jie Xue (Arabian Journal of Geosciences, 2020)

Digestive characteristics and blood chemistry profile of triploid rainbow trout Oncorhynchus mykiss: influence of body size and seasonal variation - Yuqiong Meng; Buying Han; Changzhong Li; Kangkang Qian; Xiaohong Liu; Xuemin Hu; Xu Yang; Haining Tian; Rui Ma (Fisheries Science, 2019)

Nitrogen use-inefficient oilseed rape genotypes exhibit stronger growth potency during the vegetative growth stage - Xiao Guo; Huiying He; Rong An; Yuying Zhang; Rui Yang; Lanqin Cao; Xiaoming Wu; Biyun Chen; Hui Tian; Yajun Gao (Acta Physiologiae Plantarum, 2019)

Resina draconis inhibits the endoplasmic-reticulum-induced apoptosis of myocardial cells via regulating miR-423-3p/ERK signaling pathway in a tree shrew myocardial ischemia–reperfusion model - Tian-Rui Yang; Tong Zhang; Ning-Hui Mu; Li-Bo Ruan; Jin-Lan Duan; Rong-Ping Zhang; Yun-Bo Miao (Journal of Biosciences, 2019)

Cloning and Identification of Differentially Expressed Genes Associated with Smut in Sugarcane - Xiu-Peng Song; Dan-Dan Tian; Ming-Hui Chen; Zhen-Qiang Qin; Jin-Ju Wei; Chun-Yan Wei; Xiao-Qiu Zhang; De-Wei Li; Li-Tao Yang; Yang-Rui Li (Sugar Tech, 2018)

Alzheimer’s Disease Risk Variant rs2373115 Regulates GAB2 and NARS2 Expression in Human Brain Tissues - Guiyou Liu; Tao Wang; Rui Tian; Yang Hu; Zhifa Han; Pingping Wang; Wenyang Zhou; Peng Ren; Jian Zong; Shuilin Jin; Qinghua Jiang (Journal of Molecular Neuroscience, 2018)

SNAI1, an endothelial–mesenchymal transition transcription factor, promotes the early phase of ocular neovascularization - Jia-Xing Sun; Tian-Fang Chang; Man-Hong Li; Li-Juan Sun; Xian-Chun Yan; Zi-Yan Yang; Yuan Liu; Wen-Qin Xu; Yang Lv; Jing-Bo Su; Liang Liang; Hua Han; et al. (Angiogenesis, 2018)

An adaptive sampling approach to reduce uncertainty in slope stability analysis - Jing-Sen Cai; Tian-Chyi Jim Yeh; E-Chuan Yan; Rui-Xuan Tang; Jet-Chau Wen; Shao-Yang Huang (Landslides, 2018)

Nutrient Decomposition Rate and Sugarcane Yield as Influenced by Mung Bean Intercropping and Crop Residue Recycling - Tie-Guang He; Li-Rong Su; Yang-Rui Li; Tian-Ming Su; Fang Qin; Qin Li (Sugar Tech, 2018)

Microsatellite records for volume 10, issue 1 - Ai-Qing Yu; Chengxin Fu; Chongbo He; Fei Liu; Guo-Hua Ding; Hongman Hou; Jian Zhao; Jianmin Yang; Jiansheng Wang; Kun-ci Chen; Lan-lan Zhang; Pan Li; et al. (Conservation Genetics Resources, 2018)

Three new polyketides from the marine sponge-derived fungus Trichoderma sp. SCSIO41004 - Xiaoyan Pang; Xiuping Lin; Yongqi Tian; Rui Liang; Junfeng Wang; Bin Yang; Xuefeng Zhou; Kumaravel Kaliyaperumal; Xiaowei Luo; Zhengchao Tu; Yonghong Liu (Natural Product Research, 2018)

A new immunosuppressive pregnane glycoside from aqueous fraction of Epigynum cochinchinensis - Zong Wan; Yuan-Cheng Yao; Fei Gao; Sheng-Bao Cai; Afsar Khan; Tian-Rui Zhao; Xiao-Yan Yang; Jian Fan; Sheng-Yan Qian; Jian-Xin Cao; Gui-Guang Cheng (Natural Product Research, 2017)

TQ-B3203, a potent proliferation inhibitor derived from camptothecin - Xiquan Zhang; Meng Cao; Jing Xing; Fei Liu; Ping Dong; Xin Tian; Hongjiang Xu; Laifang Zhang; Hongmei Gu; Ling Yang; Rui Li; Ming Zheng; et al. (Medicinal Chemistry Research, 2017)

Association of ACYP2 and TSPYL6 Genetic Polymorphisms with Risk of Ischemic Stroke in Han Chinese Population - Yiqian Liang; Rui Zhang; Shuo Zhang; Guofa Ji; Puyu Shi; Tian Yang; Feng Liu; Jing Feng; Chunqi Li; Dangshe Guo; Mingwei Chen (Molecular Neurobiology, 2017)

Remains of trilobites and other species discovered in a volcanic ash bed of the end-Permian, Yangtze craton, South China - Zejin Shi; Leixun Lu; Guan Yin; Hongyu Long; Wenjie Li; Huaixin Yang; Rui Cao; Xuesong Tian; Qian Tan; Kun Wang; Yong Wang; Yaming Tian (International Geology Review, 2017)

Hydrogen‐rich water regulates effects of ROS balance on morphology, growth and secondary metabolism via glutathione peroxidase in Ganoderma lucidum - Ang Ren; Rui Liu; Zhi‐Gang Miao; Xue Zhang; Peng‐Fei Cao; Tian‐Xi Chen; Chen‐Yang Li; Liang Shi; Ai‐Liang Jiang; Ming‐Wen Zhao (Environmental Microbiology, 2017)
Summary Ganoderma lucidum is one of the most important medicinal fungi, but the lack of basic study on the fungus has hindered the further development of its value. To investigate the roles of the redox system in G. lucidum , acetic acid (HAc) was applied as a reactive oxygen species (ROS) stress inducer, and hydrogen‐rich water (HRW) was used to relieve the ROS stress in this study. Our results demonstrate that the treatment of 5% HRW significantly decreased the ROS content, maintained biomass and polar growth morphology of mycelium, and decreased secondary metabolism under HAc‐induced oxidative stress. Furthermore, the roles of HRW were largely dependent on restoring the glutathione system under HAc stress in G. lucidum . To provide further evidence, we used two glutathione peroxidase (GPX)‐defective strains, the gpxi strain, the mercaptosuccinic acid (MS, a GPX inhibitor)‐treated wide‐type (WT) strain, and gpx overexpression strains for further research. The results show that HRW was unable to relieve the HAc‐induced ROS overproduction, decreased biomass, mycelium morphology change and increased secondary metabolism biosynthesis in the absence of GPX function. The gpx overexpression strains exhibited resistance to HAc‐induced oxidative stress. Thus, we propose that HRW regulates morphology, growth and secondary metabolism via glutathione peroxidase under HAc stress in the fungus G. lucidum . Furthermore, our research also provides a method to study the ROS system in other fungi.

Nurr1 promotes intestinal regeneration after ischemia/reperfusion injury by inhibiting the expression of p21 (Waf1/Cip1) - Guo Zu; Jihong Yao; Anlong Ji; Shili Ning; Fuwen Luo; Zhenlu Li; Dongcheng Feng; Yiqi Rui; Yang Li; Guangzhi Wang; Xiaofeng Tian (Journal of Molecular Medicine, 2017)

Early postnatal stress suppresses the developmental trajectory of hippocampal pyramidal neurons: the role of CRHR1 - Rui Liu; Xiao-Dun Yang; Xue-Mei Liao; Xiao-Meng Xie; Yun-Ai Su; Ji-Tao Li; Xiao-Dong Wang; Tian-Mei Si (Brain Structure and Function, 2016)

Activation of Autophagy Contributes to the Angiotensin II-Triggered Apoptosis in a Dopaminergic Neuronal Cell Line - Qing Gao; Teng Jiang; Hong-Rui Zhao; Liang Wu; You-Yong Tian; Zhou Ou; Li Zhang; Yang Pan; Jie Lu; Ying-Dong Zhang (Molecular Neurobiology, 2016)

Identification of a Novel Rat NR2B Subunit Gene Promoter Region Variant and Its Association with Microwave-Induced Neuron Impairment - Li-Feng Wang; Da-Wei Tian; Hai-Juan Li; Ya-Bing Gao; Chang-Zhen Wang; Li Zhao; Hong-Yan Zuo; Ji Dong; Si-Mo Qiao; Yong Zou; Lu Xiong; Hong-Mei Zhou; et al. (Molecular Neurobiology, 2016)

Surface display of the thermophilic lipase Tm1350 on the spore of Bacillus subtilis by the CotB anchor protein - Huayou Chen; Rui Tian; Zhong Ni; Qing Zhang; Tianxi Zhang; Zhi Chen; Keping Chen; Shengli Yang (Extremophiles, 2015)

Decreased expression of microRNA-125a-3p upregulates interleukin-23 receptor in patients with Hashimoto’s thyroiditis - Huiyong Peng; Yingzhao Liu; Jie Tian; Jie Ma; Xinyi Tang; Jun Yang; Ke Rui; Yue Zhang; Chaoming Mao; Liwei Lu; Huaxi Xu; Shengjun Wang (Immunologic Research, 2015)

Distance effect of matrix attachment regions on transgene expression in stably transfected Chinese hamster ovary cells - Jun-He Zhang; Xiao-Yin Wang; Tian-Yun Wang; Fang Wang; Wei-Hua Dong; Li Wang; Chun-Peng Zhao; Shu-Jie Chai; Rui Yang; Qin Li (Biotechnology Letters, 2014)

Preparation and Characteristics of Sugarcane Low Alcoholic Drink by Submerged Alcoholic Fermentation - Gan-Lin Chen; Feng-Jin Zheng; Bo Lin; Tian-Shun Wang; Yang-Rui Li (Sugar Tech, 2013)

Constructing genetic linkage maps for Pinus elliottii var. elliottii and Pinus caribaea var. hondurensis using SRAP, SSR, EST and ISSR markers - Hui-xiao Yang; Rui Luo; Fen-cheng Zhao; Tian-yi Liu; Chun-xin Liu; Shao-wei Huang (Trees, 2013)

Estimations of net primary productivity and evapotranspiration based on HJ-1A/B data in Jinggangshan city, China - Rong-hua Zhang; Rui Sun; Jun-ping Du; Ting-long Zhang; Yao Tang; Hong-wei Xu; Sheng-tian Yang; Wei-guo Jiang (Journal of Mountain Science, 2013)

Involvement of dopamine D2 receptors activation in ischemic post-conditioning-induced cardioprotection through promoting PKC-ε particulate translocation in isolated rat hearts - Jun Gao; Jin Guo; Hongxia Li; Shuzhi Bai; Hong Li; Bo Wu; Lina Wang; Yuhui Xi; Ye Tian; Guangdong Yang; Rui Wang; Lingyun Wu; et al. (Molecular and Cellular Biochemistry, 2013)

Petrogenesis and tectonics of late Permian felsic volcanic rocks, eastern Qiangtang block, north-central Tibet: Sr and Nd isotopic evidence - Hong-Rui Zhang; Tian-Nan Yang; Zeng-Qian Hou; Yu-Cai Song; Yan Ding; Xian-Feng Cheng (International Geology Review, 2013)

Effect of Long-Term Vinasse Application on Physico-chemical Properties of Sugarcane Field Soils - Ze-Pu Jiang; Yang-Rui Li; Guang-Po Wei; Qing Liao; Tian-Ming Su; Yan-Cheng Meng; Hai-Ying Zhang; Chang-Yan Lu (Sugar Tech, 2012)

Macronutrients Absorption and Surface Runoff Losses Under Different Fertilizer Treatments in Sugarcane Field - Tian-Ming Su; Yang-Rui Li; Guang-Po Wei; Ze-Pu Jiang; Qing Liao; Shu-Biao Zhu (Sugar Tech, 2012)

Isolation and characterization of fifteen novel microsatellite loci in golden mandarin fish (Siniperca scherzeri) Steindachne - Min Yang; Xu-Fang Liang; ChangXu Tian; Yasmeen Gul; YaQi Dou; Liang Cao; Rui Yu (Conservation Genetics Resources, 2012)

Involvement of calcium-sensing receptor in oxLDL-induced MMP-2 production in vascular smooth muscle cells via PI3K/Akt pathway - Hong-Xia Li; Fan-Juan Kong; Shu-Zhi Bai; Wen He; Wen-Jing Xing; Yu-Hui Xi; Guang-Wei Li; Jin Guo; Hong-Zhu Li; Ling-Yun Wu; Rui Wang; Guang-Dong Yang; et al. (Molecular and Cellular Biochemistry, 2012)

Multiple amino acid variations in the nonstructural proteins of swine Japanese encephalitis virus alter its virulence in mice - Rui Wu; Yongxiang Tian; Junhua Deng; Keli Yang; Wangwang Liang; Rui Guo; Zhengying Duan; Zewen Liu; Danna Zhou; Diping Xu (Archives of Virology, 2011)

Evaluation of Genetic Manipulation Strategies on d-Lactate Production by Escherichia coli - Li Zhou; Zhi-Rui Zuo; Xian-Zhong Chen; Dan-Dan Niu; Kang-Ming Tian; Bernard A. Prior; Wei Shen; Gui-Yang Shi; Suren Singh; Zheng-Xiang Wang (Current Microbiology, 2011)

Involvement of the ornithine decarboxylase/polyamine system in precondition-induced cardioprotection through an interaction with PKC in rat hearts - Ya-Jun Zhao; Wei-Hua Zhang; Chang-Qing Xu; Hong-Zhu Li; Li-Na Wang; Hong Li; Yi-Hua Sun; Yan Lin; Li-Ping Han; Li Zhang; Yie Tian; Rui Wang; et al. (Molecular and Cellular Biochemistry, 2009)

Chemical constituents from the fruits of Hippophae rhamnoides - Rui-Xia Zheng; Xu-Dong Xu; Ze Tian; Jun-Shan Yang (Natural Product Research, 2009)

Deglycosylation altered the gating properties of rNav1.3: glycosylation/deglycosylation homeostasis probably complicates the functional regulation of voltage-gated sodium channel - Qing Xu; Hui-Wen Cheng; Hui-Qiong He; Zhi-Rui Liu; Ming He; Hong-Tian Yang; Zhi-Lei Zhou; Yong-Hua Ji (Neuroscience Bulletin, 2008)

The impact of cropland conversion on environmental effect in the Loess Plateau: a pilot study based on the national experimental bases - Wang Fei; Li Rui; Jiao Feng; Yang Qingke; Tian Junliang (Journal of Geographical Sciences, 2005)